2016
DOI: 10.1111/ffe.12482
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of adjacent small defects on the fatigue limit of a medium carbon steel

Abstract: Structural steels contain various material irregularities and natural defects which cause local stress concentrations from which fatigue cracks tend to initiate. Two defects in close proximity to each other may affect local stress distributions, and thus, begin to interact. In this paper, the effect of interacting small cracks on the fatigue limit is systematically investigated in a medium carbon steel. The growth of interacting cracks, as well as the characteristics of non‐propagating cracks and microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…It has been reported that for various metallic materials, the fatigue limit as a crack‐growth threshold can accurately be predicted by the area parameter model . This model states that Δ Κ th at a stress ratio of −1 depends on the size of the initial crack or defect and the hardness of the material, expressed by the following equation: normalΔΚth=3.3×103()italicHV+120area1/3. The unit is MPa m for Δ Κ th .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that for various metallic materials, the fatigue limit as a crack‐growth threshold can accurately be predicted by the area parameter model . This model states that Δ Κ th at a stress ratio of −1 depends on the size of the initial crack or defect and the hardness of the material, expressed by the following equation: normalΔΚth=3.3×103()italicHV+120area1/3. The unit is MPa m for Δ Κ th .…”
Section: Resultsmentioning
confidence: 99%
“…This characteristic debonding behavior of MnS inclusions was independently confirmed by Maciejewski [13]. Åman et al [14] investigated the effects of interacting microstructural defects on the fatigue limit for a medium carbon steel. The investigations showed the fundamental influence of the underlying microstructure on the fatigue crack nucleation and short crack behavior.…”
Section: Introductionmentioning
confidence: 69%
“…Furthermore, they concluded that the largest microstructural defect determines the fatigue limit. Based on the experimental works [9][10][11][12][13][14], it is possible to extract the following key points: (a) the investigated martensitic steels SAE 4150 and SAE 4140 show fatigue crack nucleation on free surfaces as well as at oxidic and sulfidic inclusions with varying sizes, shapes and orientations to loading axis, (b) the MnS inclusions reveal a complex delamination behavior in case of transversal loading and (c) the lower bound of fatigue properties is controlled by the maximum size of non-metallic inclusions within the high stressed volumes [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This equation is widely used for the prediction of the fatigue limit of numerous metallic materials with small defects and cracks. [30][31][32][33][34][35][36][37] It is worth noting that the model has been proven to give an accurate forecast of the fatigue limit of the Ti-6Al-4V alloy with small defects and cracks of diverse sizes and dimensions. [38,39] In the prior study by the author et al, the local R value was calculated according to the residual stress distribution in Equation 2, thereby enabling the successful prediction of the fatigue limit of an FOD specimen.…”
Section: Discussionmentioning
confidence: 99%